Eficacia y sostenibilidad del uso familiar del agua de lluvia en comunidades rurales de la carretera Iquitos-Nauta. Loreto, 2024 - Mananita Sanchez, Alix Melissa (2025)
The present research, of a descriptive, exploratory, explanatory type and with a non experimental cross-sectional design, evaluated the effectiveness and sustainability of family use of rainwater to satisfy drinking water and sanitation needs in inhabitants of Km 31-32 of the Iquitos highway. -Nauta. The representative sample included 100 families benefiting from rainwater harvesting systems. Structured surveys were applied with a Cronbach's Alpha reliability coefficient of 0.757. For the inferential analysis, the normality of the data was determined using the Kolmogorov-Smirnov test, observing that the dimensions analyzed did not have a normal distribution, which justified the use of the Spearman correlation test. The results revealed that rainwater constitutes an essential resource in rural communities, satisfying domestic and drinking needs, reducing dependence on traditional sources and promoting more efficient management of local resources. However, limitations were identified in the storage and treatment infrastructure, compromising the quality of water for human consumption and highlighting the need for technological optimizations. The implementation of these systems generated tangible benefits such as reducing family costs, improving living conditions and strengthening social cohesion. Furthermore, it is perceived as an economically viable strategy that encourages community participation and the strengthening of the social fabric. The study concluded that rainwater has a high potential for replicability in other rural communities, although its long-term sustainability requires public policies that promote technical training, access to appropriate technologies, and project financing. Likewise, a significant correlation was identified between rainwater use patterns and its economic viability, which shows direct benefits for families. However, the absence of significant relationships with other dimensions suggests the need to investigate additional factors to improve comprehensive water resource management.